A new disordered langbeinite‐type compound, K2Tb1.5Ta0.5P3O12, and Eu3+‐doped multicolour light‐emitting properties. Issue 2 (30th January 2019) - Xue, Ya-Li; Zhao, Dan; Zhang, Shi-Rui; Li, Ya-Nan; Fan, Yan-Ping
Abstract : A new langbeinite‐type phosphate, K2 Tb1.5 Ta0.5 (PO4 )3, is reported. Under near‐UV light excitation, Eu 3+ ‐doped samples, i.e. K2 Tb1.5– x Ta0.5 (PO4 )3 : x Eu, show a continuously changing emitting colour from green to red along with the x value. Abstract : For the first time, a new langbeinite‐type phosphate, namely potassium terbium tantalum tris(phosphate), K2 Tb1.5 Ta0.5 (PO4 )3, has been prepared successfully using a high‐temperature flux method and has been structurally characterized by single‐crystal X‐ray diffraction. The results show that its structure can be described as a three‐dimensional open framework of [Tb1.5 Ta0.5 (PO4 )3 ]∞ interconnected by K + ions. The Tb III and Ta V cations in the structure are disordered and occupy the same crystallographic sites. The IR spectrum, the UV–Vis spectrum, the morphology and the Eu 3+ ‐activated photoluminescence spectroscopic properties were studied. A series of Eu 3+ ‐doped phosphors, i.e. K2 Tb1.5– x Ta0.5 (PO4 )3 : x Eu 3+ ( x = 0.01, 0.03, 0.05, 0.07, 0.10), were prepared via a solid‐state reaction and the photoluminescence properties were studied. The results show that under near‐UV excitation, the luminescence colour can be tuned from green through yellow to red by simply adjusting the Eu 3+ concentration from 0 to 0.1, because of the efficient Tb 3+ →Eu 3+ energy‐transfer mechanism.